The Use of Complex Additives for the Formation of Corrosion- and Wear-Resistant Epoxy Composites - Andriy Buketov; Oleksandr Sapronov; Mykola Brailo; Danylo Stukhlyak; Serhii Yakushchenko; Natalia Buketova; Anna Sapronova; Vitalii Sotsenko (Advances in Materials Science and Engineering)
The corrosion resistance and hydroabrasive resistance of the developed epoxy composite coatings are investigated in this paper. The analysis of the penetration index change after τ = 50–150 days of immersion in a water medium and 10% sulfuric acid solution is carried out. The optimal ratio of the modifier and nanodispersed (Si3N4, Al2O3, AlN, and TiN) and fibrous (viscose, polyamide, matka silk, rong, and cashmere) fillers in the epoxy binder is determined. It was allowed to slow down the process of electrochemical reaction on the metal surface. The penetration of aggressive media in such a coating during the time t = 150 days is 0.8–2.8%. It is 1.5–2 times lower than the similar indexes of the initial epoxy matrix. The rational combination of the fibrous filler (wool, acrylic PAN, and cashmere), modifier, and nanodispersed (Si3N4, AlF3, IH, and ZrH) filler in the epoxy binder is found, which allows to provide optimum indexes of wear rate. The wear rate under the action of a hydroabrasive of such a coating is I = 0.20%, which is 4 times lower than the similar indexes of the initial epoxy matrix. The wear mechanism of such coatings is caused by the physical and mechanical processes of microcutting and plastic deformation of the surface layer of the material.